Increasing Return: Supply Chain Economic in the Development of Indonesia’ Defense Industry Independence - Endro Tri Susdarwono (IAIN Madura, 2021)
The purpose of this study discusses increasing returns: economic supply chain in the development of the independence of the Indonesian defense industry. This research is a qualitative research, the type of research uses a comprehensive analytical study and analytical normative approach. The concept of supply chain economics shows that integration and harmony between engineering fields with economic and social science are very important to be reconstructed to produce Indonesia's best economic competition performance. Independence in making defense equipment must continue to be utilized and developed. By making its own defense equipment, Indonesia will get various benefits, from the economic benefits of the emergence of defense industry clusters that will help drive economic growth, provide plenty of jobs, and enhance technological capabilities. Technology is an aspect that can distinguish a country's defense capabilities from other countries. If the mastery of technology can be carried out by defense industry players in Indonesia, this will be a big advantage for Indonesia's defense forces. Guiding corporations or defense companies is as important as industrial coaching. Defense industry companies actually become a vehicle and the spearhead of the formation of an independent, professional, efficient, modern, and innovative defense industry as well as implementing good corporate governance. Corporate development can include aspects of strategy, managerial, production, efficiency, and marketing